ANALISIS TINGKAT EFEKTIVITAS DAN KONTRIBUSI PENDAPATAN ASLI TERHADAP ANGGARAN PENDAPATAN DAN BELANJA DAERAH DI KABUPATEN BERAU: ANALISIS TINGKAT EFEKTIVITAS DAN KONTRIBUSI PENDAPATAN ASLI TERHADAP ANGGARAN PENDAPATAN DAN BELANJA DAERAH DI KABUPATEN BERAU - Verenika Geovani (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2020)
The purpose of this study refers to the formulation of the problem raised by the researcher, namely: to find out the effectiveness of management and the contribution of the Local Own-source Revenue to Berau district's Local government budget on average from 2011 to 2018. This study aims to provide information to the Berau District Government regarding the effectiveness of the management and contribution of the Regional Original Revenue to the Berau Regency Regional Revenue and Expenditures on average from 2011 to 2018. The results showed that the first hypothesis stating the management of the Berau Regency's Original Revenue, on average during 2011 to 2018 was